Medication Safety as an Effort to Prevent Medication Errors in Midwifery - Nina Zuhana; Suparni Suparni; Yulian Wahyu Permadi (Sriwijaya Journal of Medicine, 2024)
Patient safety is defined as an effort to prevent things that endanger patients in the process of administering drugs. Overall patient safety or prevention and reduction of errors of various risks resulting from such errors. During the process of health services, especially in the treatment of patients, mistakes can be made by health workers. The incidence of Drug Error is a measure of patient safety achievement. The purpose of this study was to analyze the implementation factors of medication safety in an effort to prevent drug errors in obstetrics. The research design chosen is qualitative . This research will be carried out at RSIA Aisyiyah on midwives who work in the inpatient room. Data collection techniques in this study conducted in-depth interviews with 10 informants consisting of midwives in the treatment room. Data analysis is carried out to process qualitative data. Some factors that influence the application of patient safety principles in hospital X include leadership factors, namely lack of supervision from the leadership, lack of human resources for health servants both nurses and pharmacy personnel, workplace environmental factors that are less conducive, unavailability of SPO drug administration with principle 7 correct, socialization that is not carried out consistently and continuously and does not run training or training programs. Some suggestions that may be considered by hospital X in order to provide safe services and in accordance with patient safety principles in drug administration.